Shikhara of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Details of the shekhari type (multi-spired) shikhara (superstructure) of the Bhandasar Temple. The bands on the cardinal directions of the shikhara have three rows of aedicules, which are miniatures of the actual shikhara. At the bottom of these miniature shikharas are motifs of elephants and vyala (mythical composite figures). At the topmost level, all these vertical bands are capped by a ribbed disc known as the amalaka.